PENGARUH CONTENT MARKETING DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA BISNIS SKINCARE - Chicy Widatama Putri; Nayla Martasya (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
Content marketing and brand image are two important elements in influencing consumer purchasing decisions. Content marketing focuses on providing informative, relevant, and engaging content to build trust, increase brand awareness, create emotional engagement, and provide information that helps consumers make informed decisions. Meanwhile, a strong brand image plays a vital role in building trust, creating loyalty, providing differentiation in the market, and strengthening emotional connections with consumers. The combination of these two strategies allows companies to not only drive purchases but also build long-term relationships with consumers. With proper management, content marketing and brand image can create significant added value for companies in a competitive market.